If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14(t + -6) + 4t = 6(3t + 4) + -11 Reorder the terms: 14(-6 + t) + 4t = 6(3t + 4) + -11 (-6 * 14 + t * 14) + 4t = 6(3t + 4) + -11 (-84 + 14t) + 4t = 6(3t + 4) + -11 Combine like terms: 14t + 4t = 18t -84 + 18t = 6(3t + 4) + -11 Reorder the terms: -84 + 18t = 6(4 + 3t) + -11 -84 + 18t = (4 * 6 + 3t * 6) + -11 -84 + 18t = (24 + 18t) + -11 Reorder the terms: -84 + 18t = 24 + -11 + 18t Combine like terms: 24 + -11 = 13 -84 + 18t = 13 + 18t Add '-18t' to each side of the equation. -84 + 18t + -18t = 13 + 18t + -18t Combine like terms: 18t + -18t = 0 -84 + 0 = 13 + 18t + -18t -84 = 13 + 18t + -18t Combine like terms: 18t + -18t = 0 -84 = 13 + 0 -84 = 13 Solving -84 = 13 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 12/5=6x | | 3v-15=36 | | 9p-7p= | | 3(a-5)=-10 | | (1-1/n)(1-2/n) | | 0.25x^2-8x+64=0 | | 4y+4y=7y-1 | | 5(x+10)=40 | | 5(x-4)=3x-7 | | 36.90=9 | | x-3=-27 | | 9p-7p+4p-6p= | | 3x/4=9/2 | | 9y^2+54y+0=0 | | 9x+8=4x-3 | | -3=-27 | | -2(2x-4)+8x-4= | | -12=-3/4z | | 17q-14xq=11q | | 3x(t-3)=27 | | x/-11=5 | | F=9/5x+32 | | 9x-(2x-1)=37 | | 36/(2x)=6 | | 5+x=-22 | | 5(7b-6)=110 | | -2(5s-6)-12=-2(9s+4)-3 | | 36/2x=6 | | -1.3+2.7=.2y | | -13x+22=37 | | 7/3a=14 | | y=-9x+44 |